2022
DOI: 10.3389/fmed.2022.976863
|View full text |Cite
|
Sign up to set email alerts
|

Critical reflection on required service to the community propels prospective medical students toward higher empathy, compassion, and bias mitigation but are these gains sustainable?

Abstract: PurposeWe observed increased cognitive empathy and reflective capacity scores when prospective medical students wrote critical reflections on mandatory team service-learning in a Medical Humanities course, but these findings did not include a control group. Here we compare these survey results in similar courses with and without required service-learning.MethodsForty-three prospective medical students completed a Medical Humanities course requiring critical reflection on team service-learning. In comparison, 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 38 publications
0
18
0
Order By: Relevance
“…Afterward, students discussed the advantages and disadvantages of using ChatGPT and wrote a critical reflection. They can inspire and evolve new insights and understanding that support their professional development through dialogue and critical reflection 2. Three guiding questions were provided: What questions will you ask to understand what is happening in the family?…”
Section: Learning Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Afterward, students discussed the advantages and disadvantages of using ChatGPT and wrote a critical reflection. They can inspire and evolve new insights and understanding that support their professional development through dialogue and critical reflection 2. Three guiding questions were provided: What questions will you ask to understand what is happening in the family?…”
Section: Learning Activitymentioning
confidence: 99%
“…They can inspire and evolve new insights and understanding that support their professional development through dialogue and critical reflection. 2 Three guiding questions were provided: What questions will you ask to understand what is happening in the family? What nursing interventions will you provide to the family?…”
Section: Learning Activitymentioning
confidence: 99%
“…Studies have been conducted utilising the RPQ with medical students ( Bari et al, 2021 ; Horst et al, 2019 ; Khoshgoftar & Barkhordari-Sharifabad, 2023a , 2023b ; Lee et al, 2023 ; Rogers et al, 2019 ; Schwartz et al, 2020 ; Van Winkle et al, 2021 , 2022 ), surgeons/physicians ( Aitken et al, 2021 ; Whelehan, Conlon & Ridgway, 2021 ), nurses ( Aitken et al, 2021 ; Al-Osaimi, 2022 ; Gabrielsson et al, 2022 ; Gustafsson et al, 2020 ; Khalil & Hashish, 2022 ), psychologists ( Sadusky & Spinks, 2022 ), allied health professionals ( Aurora, Mawren & Fullam, 2023 ; Or & Golba, 2023 ; Parrott et al, 2023 ), pre-service teachers ( Day, Webster & Killen, 2022 ; Fuertes-Camacho, Dulsat-Ortiz & Alvarez-Canocas, 2021 ), qualified teachers ( Chen & Chen, 2022 ; Gross, 2020 ; Moeder-Chandler, 2020 ), and sport coaches ( Da Silva et al, 2022 ). In these studies the RPQ has been used for a range of purposes, such as assessment of the reliability of the RPQ scales ( e.g ., Gustafsson et al, 2020 ), comparison between different sub-groups of participants ( e.g ., Day, Webster & Killen, 2022 ), and comparison across different time points to explore student development ( e.g ., Van Winkle et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“… Van Winkle et al (2021) have published work that demonstrates how the RPQ can be used as part of an evaluation of teaching methods ( Horst et al, 2019 ; Schwartz et al, 2020 ; Van Winkle et al, 2021 , 2022 ). For example, Van Winkle et al (2021) found that self-reported reflective practice and a self-report empathy measure significantly increased for most medical students enrolled in a 4-month online course that included activities designed to facilitate the development of reflective practice.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation